Analysis Match Factor Loader and Hauler for Activities Overburden Removal Using the Queue Method at PT. Andalan Artha Primanusa Jobsite PT. Budi Gema Gempita, South Sumatera Province - Rahmad Fikri; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2024)
Abstract.  PT. Andalan Artha Primanusa (AAP) is a company engaged in coal production. In November 2022 PT. AAP set an overburden (OB) production target of 817.343 bcm/month, with actual achievement of 453.000 bcm/month or around 55,4% of the planned production target. Based on observations in the field, one of the factors that can hamper production is fleet mismatch (digging equipment waiting for loading) and the unit circulating time is quite high, the XCMG ADT's circulation time is 13.5 minutes, which causing the work of the tool to be less than optimal, as well as other aspects such as unfavorable hauling road conditions so that the operator has to reduce speed which is one of the causes of the high circulation time. The purpose of this research is to analyze the actual unit production, to analyze the value of fleet match factor and to analyze production achievement in overburden removal activities using queuing theory. Based on the results of queuing theory analysis, the number of ADT needed is in accordance with the level of excavator service, namely 7 units of ADT for each fleet and the overburden production is achieved, namely 322.513,6 bcm/month or 39,4% of the target set. Because after setting the queuing theory the production target had not been achieved, the researchers optimized production by using cycle time and the best work efficiency value of the unit, as well as adding 2 units of ADT for each fleet, so that the production of conveyance became 955.839,6 bcm/month or around 116,94% of the target that has been set.Keywords: Match Factor, Overburden, Production, Queuing Theory